The quality of life of patients with nephrolithiasis after the endourological removal of calculi from the urinary tract - Słota, Diana; Wasilewski, Tadeusz Paweł; Goniewicz, Mariusz; Długoborska, Klaudia (Journal of Education, Health and Sport, 2019)
Introduction. Nephrolithiasis consists of the production and retention of calculi in the urinary tract. It is being diagnosed in an increasing number of people of any age, and is one of the most common ailments in the world. Depending on a number of factors, it can be found in 5–20% of the population. Traditional surgeries are being replaced by less invasive methods of treatment. The relation between the endourological removal of calculi from the urinary tract and the assessment of the quality of life of patients who have undergone such procedures is an interesting topic worth analysing. In the 21st century, quality of life became the indicator of the efficacy of many therapies and procedures. It is associated with the quality of treatment, reflecting a better and longer life with the disease. Objective. The objective of this study is to demonstrate the quality of life of the surveyed patients with nephrolithiasis after the endourological removal of calculi from the urinary tract. Materials and methods. The group of surveyed individuals qualified for statistical analysis included 120 people diagnosed with nephrolithiasis. The patients underwent the procedure of the endourological removal of calculi from the urinary tract in 2015 in three hospitals in eastern Poland. Among the respondents, 48% of them underwent extracorporeal shock wave lithotripsy (ESWL), 31% had percutaneous nephrolithotripsy (PCNL), and 21% had uretherorenoscopic lithotripsy (URS). To evaluate the quality of life, a research tool was devised based on an abbreviated version of the Polish adaptation of the WHOQOL – BREF questionnaire. Also, a personal questionnaire prepared by the author was used. Results and conclusions. The analysis of the collected materials demonstrated the impact of the endourological removal of calculi from the urinary tract on the quality of life of the hospitalised patients. Differences were identified in individuals’ general rating of quality of life (57% of respondents were satisfied) and patients’ general satisfaction with their health (47.5% of respondents were satisfied) after the procedure. Significant differences were identified in each of the studied fields: physical, psychological, social and environmental. A statistically significant correlation of p<0.05 was observed between the respondents’ rating of their quality of life in individual fields, and their gender and age, place of residence, education and type of procedure. Key words: nephrolithiasis, quality of life (QoL), WHOQOL – BREF, endourological removal of calculi